2017
DOI: 10.1177/0956462417719643
|View full text |Cite
|
Sign up to set email alerts
|

How can those engaging in chemsex best be supported? An online survey to gain intelligence in Greater Manchester

Abstract: Reports of sexualised drug taking (chemsex) have increased significantly in recent years. There is currently limited intelligence on chemsex outside of London. An anonymous survey was promoted via several sources including voluntary services and a sexual health clinic in order to establish the risks associated with chemsex, and how support services can best be tailored to meet the needs of those in Greater Manchester, UK. Quantitative and qualitative data were collected on demographics, drug use, sexual practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 4 publications
2
21
0
6
Order By: Relevance
“…This result corroborates those of a recent online survey conducted in Australia among MSM showing that willingness to use PrEP was associated with reporting higher risk practices 31 and those of a study showing that PrEP adherence was higher among MSM and transgender women who reported more risk behaviors. 32 As already seen in other studies, 18,33 we found that chemsex was associated with high-risk HIV exposure and hardcore sexual practices. However, it was also associated with higher HIV-risk perception.…”
Section: Discussionsupporting
confidence: 84%
“…This result corroborates those of a recent online survey conducted in Australia among MSM showing that willingness to use PrEP was associated with reporting higher risk practices 31 and those of a study showing that PrEP adherence was higher among MSM and transgender women who reported more risk behaviors. 32 As already seen in other studies, 18,33 we found that chemsex was associated with high-risk HIV exposure and hardcore sexual practices. However, it was also associated with higher HIV-risk perception.…”
Section: Discussionsupporting
confidence: 84%
“…It is therefore necessary to guarantee a safe environment in which assistance is provided in a non-judgmental manner, and where it is possible to maintain anonymity. These needs for a safe and value-neutral space are in line with previous studies in other countries [14,15,39].…”
Section: Discussionsupporting
confidence: 87%
“…Another finding from this literature review suggested the need for a non-judgmental approach by healthcare workers, especially because not all GBMSM disclosing their chemsex use have a problem that needs further support or referral. A qualitative study in Singapore [14] and an online survey in Great Manchester [39] also showed this need for a safe space and non-judgmental attitude. Especially because underlying factors such as shame, stigma, and the punitive nature of local drug laws act as a barrier to seeking professional help, or adhering to certain harm reduction strategies [14,15].…”
Section: Introductionmentioning
confidence: 95%
“…Drug use during sex, or ‘chemsex’, is a well-documented behaviour among men who have sex with men (MSM) [ 1 , 2 ]. The main type of drugs described in chemsex are drugs that stimulate sexual desire, such as crystal methamphetamine, gamma-hydroxybutyric acid (GBH)/gamma-butyrolactone (GBL), mephedrone, ecstasy (XTC) and ketamine [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%